Thermal Stability of Paraffin and Fatty Acid Mixtures - Yan, Quanying; Yue, Lihang (Asian Journal of Chemistry, 2013)
Twenty kinds of paraffin mixtures and fatty acid mixtures were prepared. Phase change temperatures of mixtures are between 20 and 30 ºC and the phase change latent heats are bigger. The changes of phase change temperatures and latent heats of the phase change materials were tested by differential scanning calorimeter after multiple heat cycle. The results of the two kinds of mixtures were compared to discuss the thermal stability. The results showed that their thermal stabilities are good after 500 cycles and the phase change temperatures and latent heats have small fluctuations, but there is no obvious rule. The thermal stability of fatty acids mixtures is better than that of paraffin materials. Paraffin mixtures and fatty acid mixtures are ideal phase change material used for the wall to storage energy because of their good stability. The results can provide reference and basis for the application of paraffin and fatty acid in the field of building energy-saving.